IDIOPATHIC HYPERALDOSTERONISM PRESENTING AS RESISTANT HYPERTENSION - Siddique, Abdul Hameed; Sharif, Hamid; Aziz, Sohail (Pakistan Armed Forces Medical Journal, 2020)
Secondary hypertension constitutes about 2-10% of all cases of hypertension. Uncontrolled hypertension or hypertension requiring control with two or more antihypertensive drugs require evaluation of secondary hypertension. Among the causes of secondary hypertension endocrinal abnormalities constitutes upto 1-2% of all cases and can be due to endogenous or exogenous hormonal imbalances. PrimaryAaldosteronism (PA) is a group of endocrine disorders in which aldosterone production is inappropriately high, autonomous of the renin-angiotensin system and not suppressed by sodium loading. Bilateral idiopathic hyperaldosteronism (IHA) and aldosterone producing adenoma (APA) are the most common subtypes of PA. It is estimated that more than 10% of patients with secondary hypertension in both general and specialty settings are a result of PA2,3. We present two cases of idiopathic hyperaldosteronism presenting as resistant hypertension.